2008
DOI: 10.1160/th08-06-0376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the venous thromboembolic risk associated with severe postpartum haemorrhage in the NOHA First cohort

Abstract: Severe postpartum haemorrhages (PPH) are responsible for maternal morbidity/mortality. Their complex management sometimes requires haemostatic supplementation, and therapeutic trials on fibrinogen or activated factor VII, which may add to the thrombotic risk, are currently being considered. Furthermore, there is a risk of venous thromboembolism (VTE) during the postpartum period, hence we studied the relationship between severe PPH and VTE in women during their first pregnancy. Among the 32,463 women enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Citations not in English were screened at this stage using Google translate. A total of 12 papers appeared to meet the inclusion criteria for this review [2536]; however, at data extraction stage it was realised that we were unable to abstract data from six papers [26, 29, 32–35] because the outcomes reported in these papers all related to management or treatments of PPH, and no maternal physical or emotional health outcomes were reported.
Fig. 1Flow diagram of the search and selection process
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Citations not in English were screened at this stage using Google translate. A total of 12 papers appeared to meet the inclusion criteria for this review [2536]; however, at data extraction stage it was realised that we were unable to abstract data from six papers [26, 29, 32–35] because the outcomes reported in these papers all related to management or treatments of PPH, and no maternal physical or emotional health outcomes were reported.
Fig. 1Flow diagram of the search and selection process
…”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics of included papers are presented in Table 3. Five studies reported the outcomes of primary PPH [25, 27, 28, 30, 31] and one reported outcomes after secondary PPH [36]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations